A polarization census of bright pulsars using the ultrawideband receiver on the Parkes radio telescope. Issue 1 (26th March 2021) - Sobey, C; Johnston, S; Dai, S; Kerr, M; Manchester, R N; Oswald, L S; Parthasarathy, A; Shannon, R M; Weltevrede, P
ABSTRACT: We present high signal-to-noise ratio, full polarization pulse profiles for 40 bright, 'slowly' rotating (non-recycled) pulsars using the new ultrawideband low-frequency (UWL; 704–4032 MHz) receiver on the Parkes radio telescope. We obtain updated and accurate interstellar medium parameters towards these pulsars (dispersion measures and Faraday rotation measures), and reveal Faraday dispersion towards PSR J1721–3532 caused by interstellar scattering. We find general trends in the pulse profiles including decreasing fractional linear polarization and increasing degree of circular polarization with increasing frequency, consistent with previous studies, while also revealing new features and frequency evolution. This demonstrates results that can be obtained using UWL monitoring observations of slow pulsars, which are valuable for improving our understanding of pulsar emission and the intervening interstellar medium. The calibrated data products are publicly available.